KINERJA ORGANISASI DALAM PELAYANAN e-KTP DI KANTOR KECAMATAN SINDUE TOMBUSABORA KABUPATEN DONGGALA - Aqib, Aqib (Katalogis, 2016)
This study aims at determining the performance of organization in the service of e-ID at the Sub-district Office of Sindue Tombusabora, Donggala. This research uses qualitative methods. The informants of this study are the apparatus and the the people in Sindue Tombusabora Sub-district, Donggala, the research data used in this study are primary and secondary data through observations and interviews towards The informants of this study are the apparatus and the the people in Sindue Tombusabora Sub-district, this research uses the theory of Agus Dwiyanto which consists of five aspects: Productivity, Quality of Service, Responsiveness, Responsibility, and Accountability. The organization performance in the service of e-ID based on the results of this research related to apparatus service is not good and still far from the expectations of society. The results of the study reveal that the performance of the apparatus is not good yet it is closely related to productivity, quality of service, responsiveness in providing the service is still very low. While the responsibility and accountability describe poor performance towards the Public Service.